Oxide-defects driven study on reliability and synaptic response characterization of logic devices - Ju, Xin (Nanyang Technological University, 2021)
The thesis discusses our studies on the key characterization issues and physical mechanisms of channel-hot carrier (CHC) stressing in reliability and variability in nanoscale MOS devices. This provides physical understanding of HCD in reliability qualification and helps reliability-aware circuits design in nanoscale CMOS technology. In addition, successful demonstration of synaptic characteristics with a logic transistor by modulating charge capture/emission kinetics in gate oxide shows the potential of realizing neuromorphic systems capable of encoding and processing complex spatiotemporal information.